2019
DOI: 10.1186/s12886-019-1184-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of machine learning for differentiation between optic neuropathies and pseudopapilledema

Abstract: Background This study is to evaluate the accuracy of machine learning for differentiation between optic neuropathies, pseudopapilledema (PPE) and normals. Methods Two hundred and ninety-five images of optic neuropathies, 295 images of PPE, and 779 control images were used. Pseudopapilledema was defined as follows: cases with elevated optic nerve head and blurred disc margin, with normal visual acuity (> 0.8 Snellen visual acuity), visual field, color vision, and pupilla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 16 publications
0
15
0
2
Order By: Relevance
“…ML has also been used to accurately differentiate between optic neuropathies and pseudopapiledema by using fundus photography. 76 …”
Section: Software-based Technologiesmentioning
confidence: 99%
“…ML has also been used to accurately differentiate between optic neuropathies and pseudopapiledema by using fundus photography. 76 …”
Section: Software-based Technologiesmentioning
confidence: 99%
“…Due to the lack of ophthalmologists in many departments, it is often necessary to use machine learning to evaluate optic disc edema. Ahn et al (46) used machine learning to distinguish between patients with optic neuropathy, pseudopapilledema (PPE), and normal subjects. A model was designed and compared with the 3 most commonly used machine learning classifiers, GoogleNet Inception V3, 19 layers of super deep convolution network from visual geometry group, and 50 layers of deep residual learning (ResNet).…”
Section: Abnormalities Of the Optic Discmentioning
confidence: 99%
“…As the structure of the optic disc is different between the nasal and temporal sides, the direction of the optic disc and whether the pathological lesion site is unilateral or bilateral are vitally important clinical data which can affect the diagnosis and determine the relative imaging and/or systematic evaluation. Several studies have shown that DLSs can accurately recognize the right or left eye in photos with optic discs (44,46). Furthermore, it can distinguish optic disc edema from normal optic disc with an average accuracy of 93%, and distinguish real optic disc swelling from pseudo-swelling with an accuracy of about 95%.…”
Section: Abnormalities Of the Optic Discmentioning
confidence: 99%
“…Mit einem ML-Modell konnten Ahn et al. zwischen geschwollenen Sehnervenköpfen aufgrund unterschiedlicher Optikusneuropathien, Pseudopapillenödemen und gesunden Sehnervenköpfen unterscheiden [ 42 ]. Zusätzlich umgingen die genannten Autoren das Problem eines kleinen Datensatzes.…”
Section: Künstliche Intelligenzunclassified